Perilaku Disolusi Ketoprofen Tersalut Gel Kitosan-Karboksimetilselulosa (CMC) - Sugita, Purwantiningsih; Achmadi, Suminar Setiati; Yundhana, Yuyu (Jurnal Natur Indonesia, 2010)
Study dissolution behaviour of ketoprofen through optimum chitosan-CMC microcapsule has been carried out. Into228.6 ml of 1.0% (w/v) chitosan solution in 1% (v/v) acetic acid, 38.1 ml of CMC solution was added with concentrationvariation of 0.075; 0.0875; and 0.10% (w/v). Afterwards, 7.62 mL of glu was added slowly under stirring, withconcentrations varied: 3; 4.5; and 6% (v/v). All mixtures were shaked for 20 minutes for homogenization. Into eachmicrocapsule mixture for ketoprofen, a solution of 2 g of ketoprofen in 250 mL of 96% ethanol was added. Everymixture was then added with 5 ml of 2% Tween-80 and stirred with magnetic stirrer for an hour at room temperature.Conversion of suspension into fine powders/granules (microcapsules) was done by using spray dryer. Thedissolution behaviour of optimum ketoprofen microcapsules were investigated in gastric and intestinal medium.Microcapsule morphology before and after dissolution as well as empty microcapsule (blank) were observed withSEM. Spray drying process had successfully coated ketoprofen in chitosan-CMC microcapsule. Optimization byusing Minitab Release 14 software showed that among the microcapsule compositions studied, CMC and glu of0.0925% (w/v) and 3.01% (v/v), respectively, optimum to coat ketoprofen at constant chitosan concentration 1.0%(w/v). Result of SEM morphology and In vitro dissolution profile showed that ketoprofen in chitosan-CMCmicrocapsule was relatively well than chitosan-guar gum microcapsule. Kinetically, dissolution of ketoprofen frommicrocapsule in intestinal pH condition was first order with release rate constant, k, of 7.285 ï‚´ 10-4 % min-1 andrelease half-time, t1/2, of approximately 15 hours.